Experiences of women receiving maternal care regarding cultural practices in selected public hospitals in the North West Province, South Africa - Khumoetsile Daphney Shopo; Tinda Rabie; Antoinette Du Preez; Petra Bester (Elsevier, 2024)
Background: Midwives providing care to a culturally diverse society must know and understand the important cultural practices for women receiving maternal care. On the part of the midwives, balancing an act of respecting cultural beliefs and practices while maintaining the professional standard of care is an art. Objective: To explore and describe the experiences of women receiving maternal care regarding cultural practices and their perception about midwives providing maternal care. Method: A phenomenological, qualitative and descriptive design approach was chosen for this study. Women receiving maternal care (antenatal and postpartum) within five public hospitals in the North West Province of South Africa, were purposively sampled. A total of fifty (n = 50) in-depth individual interviews, guided by an interview guide, were conducted in English or Setswana. The interviews were digitally audio-recorded and transcribed verbatim followed by thematic analysis. The independent co-coder also conducted data analysis to enhance rigour. Findings: Participants described specific self-care practices which are essential to them during the antenatal period. These included restricting movement and social activities, wearing loose clothing, not smoking and attending the antenatal clinic. Important cultural practices included consulting traditional healers for protection against evil spirits throughout the pregnancy journey. The cultural practices in the postnatal period involved using traditional medicines to protect the newborn as well. Conclusion: The objective of this study was achieved as the women receiving maternal care were able to share their important cultural practices during antenatal care until postnatal period, they further revealed that their cultural practices are not allowed.